KGB Man : the cold war's most notorious Soviet agent and the first to be exchanged at the Bridge of Spies - Kuhne, Cecil C., III, 1952- (New York : Knox Press, 2023)
"A thin, balding, and reclusive middle-aged Russian by the name of Rudolf Ivanovich Abel was one of the Soviet Union's most renowned spies during the Cold War of the 1950s ... until his cover was blown by an incompetent colleague who wanted to defect to the United States. This is the full account of Abel's espionage work, his dramatic apprehension, his eventual conviction and its affirmation by the United States Supreme Court, and finally, his surprising release back to Russia"--
Keywords: Abel, Rudolf, -- 1903-1971.; Abel, Rudolf, -- 1903-1971.; Spies -- Soviet Union -- Biography; Spies -- Great Britain -- Biography; Espionage, Soviet -- United States; Espionage, Soviet; Spies; Great Britain; Soviet Union; United States; Biographies; Biographies